(untitled) (Journal on Geoinformatics, Nepal, 2013)
Global Positional Systems (GPS) now is competing with traditional surveying techniques in almost all fields of geodesy and cadastral surveying after the availability of highly productive new systems such as Real Time Kinematic (RTK) systems along with the use of Global Navigation Satellite Systems (GNSS). Although the cadastral mapping of the entire Nepal was completed in 1996 using graphical survey with plane table technique, derived information from the existing maps now are outdated and do not fulfil the needs of the general public. Updating cadastral maps is not only necessary but vital in Nepal. Survey Department under the Ministry of Land Reforms & Management, Government of Nepal now has to adopt an appropriate innovative approach for cadastral mapping in the country in order to meet the growing public demands on reliable land information system, to provide speedy land administrative services as well as for overall development of the country. With continual research and development into GPS, the techniques and systems developed have become more reliable, cheaper and more productive, making GPS more attractive for a range of surveying solutions including cadastral mapping. Though high resources may be initially required for the RTK GPS technology for cadastral surveys in Nepal when compared to presently available optical surveying techniques, it would be justifiable in investing in GPS surveys. This technology, however, will not replace the existing survey techniques but it will provide another means in carrying out cadastral surveys especially in the area where the conventional technique is not economically and temporally viable. Nepalese Journal on Geoinformatics -12, 2070 (2013AD): 33-40